SERVICE QUALITY IN HANDLING PUBLIC COMPLAINTS AT THE INTEGRATED POLICE SERVICE CENTER (SPKT) OF THE SUKABUMI CITY POLICE RESORT - Prityaswari Rucita Astya; Andi Mulyadi; Dine Meigawati (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2025)
This research focuses on the quality of service provided by the Integrated Police Service Center (SPKT) of Sukabumi City Police. The purpose of this study was to determine and describe the services provided by the Integrated Police Service Center (SPKT) of Sukabumi City Police in handling public complaints. The method used is descriptive qualitative with data collection through observation, interviews and documentation. The theory used in this research is Zeithaml et al (1988) with five dimensions namely (1) tangibles, (2) reliability, (3) responsiveness, (4) assurance, and (5) empathy. In this study, researchers used non-probability sampling and purposive sampling techniques to determine informants. The results of this study indicate that based on the five dimensions, the tangibles aspect shows quite good quality even though there are still weaknesses in terms of infrastructure such as service rooms and parking lots that are still limited. The reliability dimension is quite reliable, but there is still room to improve several things such as the delivery of clearer information regarding procedures, flow, and requirements for making reports. Meanwhile, the dimensions of responsiveness, assurance, and empathy show good results with improvements.